2021
DOI: 10.3390/polym13040586
|View full text |Cite
|
Sign up to set email alerts
|

Facile Post Treatment of Ag Nanowire/Polymer Composites for Flexible Transparent Electrodes and Thin Film Heaters

Abstract: Typical polyol-based synthesis of silver nanowire employs insulating polymer as a surfactant for the silver nanowire growth, which limits direct contact between each nanowire and thus its optoelectronic properties. We herein demonstrate that a simple solvent treatment effectively removes the insulating polymer around Ag NWs, leading to significantly decreased sheet resistance (~12 Ω/sq) with an increased transmittance (81% @ T550), as compared to other post-treatments. We successfully demonstrate the transpare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Graphene, graphene oxide (GO), and reduced GO (rGO) have improved chemical, thermal, electrical, and optical stabilities of AgNW TEs, but their conformal coating processes without defects are difficult and required a high-temperature reactor or a dangerous synthesis process using toxic chemicals. Metal and metal oxide thin films such as Ni, ZnO, TiO 2 , and oxynitride can provide efficient protection from mechanical detachment and thermal, electrical, and chemical agitations, but the sputtering, electrodeposition, and atomic layer deposition equipment is also generally essential to coat these thin films on AgNW TEs. In this regard, solution-processable materials can be important choices, and thus, various materials such as MoO x , organothiols, polyvinyl alcohol, PEDOT:PSS, polydopamine, ion gel, and chitosan have been investigated for the simple and efficient protection of AgNW TEs. There were relatively limited reports on the use of MoO x and organothiols as protective layers, and their protection properties have not been fully demonstrated for various agitations. The protection ability of the MoO x coating layer was verified for chemical etching and mechanical agitations such as bending, scotch tape peel-off, and sonication and that of organothiols was also studied for thermal oxidation, sulfidation, and electrical potential. , Although polymers have been extensively explored as a solution-processable protective layer owing to their high diversity, transmittance, and film formability, their protection ability was generally focused on thermal oxidation and mechanical agitations and was not inclusively examined for chemical, electrical, and optical agitations. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene, graphene oxide (GO), and reduced GO (rGO) have improved chemical, thermal, electrical, and optical stabilities of AgNW TEs, but their conformal coating processes without defects are difficult and required a high-temperature reactor or a dangerous synthesis process using toxic chemicals. Metal and metal oxide thin films such as Ni, ZnO, TiO 2 , and oxynitride can provide efficient protection from mechanical detachment and thermal, electrical, and chemical agitations, but the sputtering, electrodeposition, and atomic layer deposition equipment is also generally essential to coat these thin films on AgNW TEs. In this regard, solution-processable materials can be important choices, and thus, various materials such as MoO x , organothiols, polyvinyl alcohol, PEDOT:PSS, polydopamine, ion gel, and chitosan have been investigated for the simple and efficient protection of AgNW TEs. There were relatively limited reports on the use of MoO x and organothiols as protective layers, and their protection properties have not been fully demonstrated for various agitations. The protection ability of the MoO x coating layer was verified for chemical etching and mechanical agitations such as bending, scotch tape peel-off, and sonication and that of organothiols was also studied for thermal oxidation, sulfidation, and electrical potential. , Although polymers have been extensively explored as a solution-processable protective layer owing to their high diversity, transmittance, and film formability, their protection ability was generally focused on thermal oxidation and mechanical agitations and was not inclusively examined for chemical, electrical, and optical agitations. , …”
Section: Introductionmentioning
confidence: 99%
“…22,23 Although polymers have been extensively explored as a solution-processable protective layer owing to their high diversity, transmittance, and film formability, their protection ability was generally focused on thermal oxidation and mechanical agitations and was not inclusively examined for chemical, electrical, and optical agitations. 29,30 Therefore, there is still a strong demand for a simple and efficient strategy to protect AgNW TEs from various external agitations, and it is also desirable to harness biorenewable materials as protective agents for the environmental sustainability. In this regard, chitin nanofibers (CNFs) and alkali lignin (AL) are considered as promising candidates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the other hand, the rapid development in the field of flexible electronics also requires that TCE materials maintain conductivity after bending and stretching, but the brittle nature hinders their applications in flexible devices. Therefore, in recent years, some promising ITO alternatives have been developed as TCE materials, including conducting polymers, [ 6 ] carbon nanotube, [ 7 ] metal nanowires, [ 8 ] and graphene. [ 9 ] These candidate materials have good properties, but the TCEs with monolithic material could not reach the performance of ITO.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports on the evaluation of the mechanical properties of Ag nanowire electrodes subjected to bending [23][24][25]. For example, Jin et al reported 2 of 8 Ag nanowire transparent electrodes for application in flexible transparent heaters; bending tests were performed to confirm the flexibility of the electrodes under 100 cycles of bending [23]. There was no significant change in resistance during bending.…”
Section: Introductionmentioning
confidence: 99%